Genetic and morphometric analyzes of Paralichthys species confirm the presence of P. brasiliensis in the Uruguayan waters. Issue 1 (1st January 2019) - Olsson, Daniela; Marquez, Alejandro; Tellechea, Javier .S.; Carvalho, Pedro Hollanda; Pereira, Alfredo N.; Norbis, Walter
ABSTRACT: Paralichthys species have high commercial value and constitute a resource for demersal fisheries in the Southwestern Atlantic Ocean. Although six species have been described based on morphological characters for the Uruguayan and Argentinean waters, only the presence of three species is accepted, being their distribution still uncertain. Genetic tools are useful for species identification as a complement of morphological characters. This paper determines the genetic and morphometric variation between three species of Paralichthys that inhabiting Uruguayan waters. The interorbital width (IN) and the length from the mouth to the dorsal fin base (SD) of P. patagonicus differed significantly from the other two species ( P. orbignyanus and P. brasiliensis ). From a morphological perspective, individuals identified as P. orbignyanus formed two different groups. Clade Po_A included those belonging to oceanic coastal waters of Uruguay and deeper waters of the Rio de la Plata together with individuals of P. brasiliensis from ItajaÃ, Santa Catarina (Brazil). Individuals collected in the Rio de la Plata coastal and beach zone formed the clade Po_B group. Genetic analysis confirmed for the first time the presence of P. brasiliensis in Uruguayan and Rio de la Plata shelf waters and extends its known distribution area further south. Discriminant scores for P. orbygnianus separate individuals in two groups corresponding to the presence of two species. Molecular and morphological analysis showed individuals in the clade Po_A includes those collected in Uruguayan waters together with those collected in northern Brazilian waters belonging to the species P. brasiliensis .